Discovery of piperidine ethers as selective orexin receptor antagonists (SORAs) inspired by filorexant. Issue 3 (1st February 2015) - Raheem, Izzat T.; Breslin, Michael J.; Bruno, Joseph; Cabalu, Tamara D.; Cooke, Andrew; Cox, Christopher D.; Cui, Donghui; Garson, Susan; Gotter, Anthony L.; Fox, Steven V.; Harrell, C. Meacham; Kuduk, Scott D.; et al.
Graphical abstract